Alternative of Soil Improvement Methods on Organic Soil Using Preloading and Vertical Piles for Embankment with Varied Heights. Case Study: Construction of Batanjung Port Access Road in Pulang Pisau Regency, Central Kalimantan - Dedy Manudianto; Noor Endah; Hardy Pangihutan Siahaan (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2023)
The Central Kalimantan is a province with great potential for economic development. Several development plans have been launched by the government, one of which is the construction of the Batanjung Industrial Estate, Batanjung Port , and its access. The Batanjung Port development plan is in line with the Central Kalimantan Provincial Spatial Plan (RTRW) for 2015-2035, and has been stipulated in the National Medium-Term Development Plan (RPJMN) 2020-2024 and the Strategic Plan of the Ministry of General Works and Public Housing for 2020-2024. Therefore, it is necessary to build an access road to the Port of Batanjung, Central Kalimantan.However, constructing new roads requires cautious construction plan considering the type of soil in Central Kalimantan Province which is dominated by soft soils and organic soils formed by weathered plants and has a high groundwater table. Problems that generally arise include the occurrence of long and large compression (settlement) and road embankment slides. Common efforts to increase the bearing capacity of organic soil in Central Kalimantan are the installation of galam wood driven piles into the soil and the use of geosynthetic such as geotextiles. Therefore, in this study a new road embankment using national road standards is planned by observing the 5-year and 50-year Flood Water Levels (FWL) in Central Kalimantan Province. The construction use mechanical soil improvement in the form of PVD, wood piles, micropile, and geotextiles for varying road embankment heights. Then the planning results are analyzed to find out the most efficient method in terms of material use.Based on the analysis, the most efficient soil improvement method is the PVD method to accelerate consolidation rather than the micropile method to reduce the amount of compression. In addition, the most efficient reinforcement is by using geotextiles instead of galam wood piles. These results can be appled to both 5-year and 50-year FWL.